O. felineus DNA extraction method for opisthorchiasis detection - I. N. Dominova; M. V. Patrushev; L. M. Ogorodova; V. V. Novitsky (Бюллетень сибирской медицины)
Opisthorchis felineus DNA extraction methods from fecal samples were compared. Comparative analysis of selected methods of DNA extraction from fecal samples containing eggs O. felineus, revealed that the most effective method for the identification of opisthorchiasis by PCR protocol is upgraded through the use of magnetic particles.